Mapping Conformational Changes in a Self-Assembled Two-Dimensional Molecular Network by Statistical Analysis of Conductance Images - Naydenov, Borislav; Torsney, Samuel; Bonilla, Alejandro Santana; Gualandi, Andrea; Mengozzi, Luca; Cozzi, Pier Giorgio; Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni); Boland, John J. (Physical Review Applied, 2019)
A self-assembled two-dimensional (2D) film of tetra-phenyl-porphyrin-4-ferrocene molecules on Au(111) is studied by STM for the presence of intra- and intermolecular correlations in the configurations of the four-pendant ferrocenyl moieties. A statistical analysis of STS images exploits the Pearson's linear correlation coefficient derived from changes in the molecular electron density across lateral positions in the molecular network as a measure of the intra- and intermolecular coupling and/or conjugation between adjacent equivalent molecular components. Density functional theory (DFT) calculation shows that these electron density changes can be assigned to conformational changes of the ferrocenyl units of the molecules. The methodology presented here can be extended to measure correlations in other 2D systems.
CRIS-Team Scopus Importer:2022-04-14